Lutein-Zezyme Nanoparticles Encapsulated in Metallophenol Networks, Their Preparation Methods and Applications
By constructing lutein-zein nanoparticles encapsulated in a metallophenol network, the problem of insufficient stability of zein nanoparticles was solved, achieving efficient delivery and improved stability of lutein, making it suitable for applications in the food industry.
Patent Information
- Application Number
- CN202610501668.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-06-30
AI Technical Summary
In existing technologies, the stability of zein nanoparticles is insufficient, resulting in low lutein delivery efficiency and failing to effectively solve the application problems of carotenoids in the food, pharmaceutical and feed fields.
A metallophenol network was constructed using zinc ions and tannic acid to coat the surface of lutein-zein nanoparticles, enhancing their stability and bioaccessibility. Lutein-zein nanoparticles coated with the metallophenol network were prepared by an antisolvent method.
It improves the stability and bioavailability of lutein, enhances the thermal stability and salt ion stability of nanoparticles, and achieves efficient protection and sustained release of lutein, making it suitable for applications in the food industry.
Smart Images

Figure CN122296470A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite nanomaterials technology, and in particular to lutein-zein nanoparticles encapsulated in a metallophenol network, their preparation methods, and applications. Background Technology
[0002] Lutein is a lipophilic, carotenoid with two hydroxyl groups and a polyene molecular structure. It is mainly found in marigolds, egg products, leafy green vegetables, corn, potatoes, and other vegetables. It possesses various physiological activities, including preventing cardiovascular disease, anti-cancer effects, enhancing immunity, delaying age-related macular degeneration, and reducing the risk of diseases caused by oxidative stress. Since the human body cannot synthesize lutein, it must be obtained from exogenous sources such as food. However, lutein has inherent limitations, including poor water solubility, sensitivity to light and heat, and low oral bioavailability, which greatly restricts its application in the food, pharmaceutical, and animal feed industries. Therefore, developing a suitable delivery system to achieve stable protection of lutein while improving its sustained-release properties and bioavailability has become an urgent technical challenge.
[0003] Zeatin possesses excellent biodegradability and biocompatibility, and can self-assemble into nanoparticles via an antisolvent method. These nanoparticles can effectively encapsulate lutein and provide some protection, demonstrating potential as food-grade active ingredient delivery carriers. However, the stability of this type of protein nanoparticle system mainly relies on hydrophobic interactions and electrostatic repulsion, resulting in poor overall structural stability. It is prone to aggregation under physiological conditions, leading to leakage of active ingredients and reduced delivery efficiency, thus presenting a significant application bottleneck.
[0004] Metallophenol networks are high-strength cross-linked networks formed by the coordination of metal ions and polyphenolic compounds. They maintain stable bonding even under harsh environments, exhibiting both excellent mechanical strength and structural stability. Currently, they are used in the food industry for the development of sustained-release carriers for active ingredients and preservative coatings for fruits and vegetables, showing promising application prospects. However, to date, there is no mature solution in existing technologies that uses metallophenol networks to coat modified protein-based nanoparticles and apply them to carotenoid delivery systems. This prevents the synergistic effect of the two technologies from solving the technical problems of insufficient stability of protein-based nanoparticles and low carotenoid delivery efficiency, thus hindering the development and application of highly stable food-grade carotenoid delivery systems. Summary of the Invention
[0005] The main objective of this invention is to provide lutein-zein nanoparticles encapsulated in a metallophenol network, along with their preparation method and applications, to address the aforementioned problems in the prior art. This invention utilizes zein as a carrier material, based on zinc ions (Zn... 2+The coordination reaction of α-carotene and tannic acid (TA) constructs a metallophenol network, which is then wrapped around the surface of lutein-zein nanoparticles to optimize the interfacial structure of zein and synergistically enhance the stability of the protein nanoparticles. This aims to enhance the lutein loading capacity of the zein carrier, while improving the physical stability and bioavailability of lutein, thus providing a technical solution for the application of carotenoids in the food field.
[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: First, the present invention provides a method for preparing lutein-zein nanoparticles encapsulated in a metallophenol network, comprising the following steps: (1) Using the antisolvent method, zein powder was dissolved in a solvent to prepare a solution, stirred evenly, lutein was added, and stirred to obtain a dispersion; the dispersion was added to water, and the hydration reaction was carried out for 100-140 min, and then rotary evaporated to obtain lutein-zein nano dispersion. (2) Take the dispersion obtained in step (1) and add tannic acid solution, then add ZnCl2 solution, mix to obtain sample dispersion, freeze dry to obtain lutein-zein nanoparticles ZLut-TZ wrapped with metallophenol network.
[0007] Preferably, the solvent in step (1) is a 65-85% ethanol solution.
[0008] Preferably, in step (1), zein powder is dissolved in an ethanol solution until the final concentration of zein is 1.5-3.5%.
[0009] Preferably, in step (1), lutein is added at a mass ratio of zein:lutein of (25-65): (0.5-1.5).
[0010] Preferably, the hydration time in step (1) is 120 min.
[0011] Preferably, in step (2), the dispersion obtained by rotary evaporation is added to an equal volume of tannic acid solutions of different concentrations; the concentration of the tannic acid solution is set according to the mass ratio of zein to tannic acid of (5-15): (0.5-2.5).
[0012] Preferably, in step (2), the ZnCl2 solution is added at a ratio of equal volume and twice the concentration of tannic acid.
[0013] Second, the present invention provides a lutein-zein nanoparticle encapsulated in a metallophenol network prepared by the preparation method described above.
[0014] Third, the present invention also provides the application of the lutein-zein nanoparticles encapsulated in the metallophenol network in the food field.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a scheme for the application of metallophenol networks in delivery technology, utilizing zein as a carrier material and based on zinc ions (Zn). 2+ A metallophenol network was constructed by coordinating phenol and tannic acid (TA) to prepare lutein-zein nanoparticles encapsulated in a metallophenol network.
[0016] 1) The synergistic effect of zein carrier and metallophenol network can effectively improve the stability of lutein. Low concentration of metallophenol network helps to enhance the thermal stability, storage stability and salt ion stability of nanoparticles, and improve the lutein encapsulation effect.
[0017] 2) The metallophenol network endows nanoparticles with a certain pH regulation ability. Under acidic conditions, the nanoparticles have uniform particle size and a compact and stable structure, which can achieve efficient protection of lutein and prevent it from premature leakage and degradation in the stomach environment. Under neutral (or weakly alkaline) conditions, the coordination effect of the metallophenol network is weakened and the structure is loose, which helps to release lutein active molecules and greatly improves the bioavailability of lutein.
[0018] 3) The raw materials used in this invention are widely available and inexpensive; the preparation method of nanoparticles is simple, easy to operate, does not require complex equipment, and is easy to promote. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a schematic diagram of the process for preparing ZLut-TZ nanoparticles; Figure 2 The effects of different concentrations of metallophenols on particle size, dispersion (PDI), and zeta potential were investigated; where A represents the effect on particle size and PDI, and B represents the effect on zeta potential. Different letters indicate significant differences in particle size, PDI, and zeta potential among samples. p <0.05); Figure 3 The effects of different concentrations of metallophenols on the encapsulation efficiency (EE) and loading capacity (LC) of lutein; Figure 4The images show microscopic images of different nanoparticles; where A is a SEM image of different nanoparticles (scale bar = 500 nm), B is a SEM-EDS image of ZLut-TZ-1 (scale bar = 1 μm), and C is a TEM image of different nanoparticles (scale bar = 500 nm). Figure 5 The fluorescence spectra of different nanoparticles are shown; among them, Free-Zein is free zein nanoparticles, Free-Lut is free lutein nanoparticles, ZLut-TZ is lutein-zein nanoparticles encapsulated by a metallophenol network prepared in Example 1, and Zein-TZ is unencapsulated lutein nanoparticles. Figure 6 Fourier transform infrared spectra of different nanoparticles; among them, Free-Zein is free zein nanoparticles, Free-Lut is free lutein nanoparticles, ZLut-TZ is lutein-zein nanoparticles encapsulated by an equal proportion of metallophenol network, Zein-TZ is unencapsulated lutein nanoparticles, and ZLut-C is lutein-zein nanoparticles. Figure 7 The changes in lutein retention rate under different heat treatment conditions of nanoparticles are shown; where A represents heat treatment at 37℃ and B represents heat treatment at 80℃. Figure 8 The changes in lutein retention rate of different nanoparticles after storage at different temperatures for 15 days were shown; where A represents storage at 4℃ and B represents storage at 25℃. Figure 9 The values represent the particle size, zeta potential, and lutein retention rate of different nanoparticles under different NaCl concentrations; where A is the particle size, B is the zeta potential, and C is the lutein retention rate. Figure 10 The values represent the particle size, zeta potential, and lutein retention rate of different nanoparticles at pH=3 and pH=7; where A is the particle size, B is the zeta potential, and C is the lutein retention rate. Figure 11 To assess the bioavailability of lutein in different nanoparticles. Detailed Implementation
[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0022] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0023] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0024] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0025] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0026] Example 1 1. Preparation of lutein-zein nanoparticles encapsulated in a metallophenol network Preparation process as follows Figure 1 As shown in the diagram, zein powder was first quantitatively added to an ethanol-water solution (75% v / v) until the final concentration of zein reached 2.5% (w / v), and the mixture was magnetically stirred until a stable protein dispersion was formed. Then, lutein powder was added at a mass ratio of 45:1 (zein:lutein) under light-protected conditions, and the mixture was magnetically stirred overnight to obtain a dispersion. 1 mL of the dispersion was injected into 10 mL of deionized water using a syringe, and hydration was carried out for 120 min. After complete hydration, the ethanol in the system was rotary evaporated to obtain a lutein-zein (Zein-Lut) nanoparticle dispersion.
[0027] A Zein-Lut dispersion was added to an equal volume of tannic acid solution. The tannic acid content in the solution was determined by setting a zein-to-tannic acid mass ratio of 10:1. This was then mixed with an equal volume of ZnCl2 solution at twice the concentration (for tannic acid) to prepare a metallophenol network-encapsulated lutein-zein nanoparticle sample dispersion (ZLut-TZ). The sample dispersion was freeze-dried at -80℃ to obtain metallophenol network-encapsulated lutein-zein nanoparticles ZLut-TZ-1. The entire preparation process was carried out at 25℃.
[0028] Example 2 Unlike Example 1, the tannic acid content in the tannic acid solution was determined by setting the mass ratio of zein to tannic acid to 10:2. The remaining steps were the same as in Example 1, and lutein-zein nanoparticles ZLut-TZ-2 encapsulated by a metallophenol network were obtained.
[0029] Example 3 Unlike Example 1, the tannic acid content in the tannic acid solution was determined by setting the mass ratio of zein to tannic acid to 10:3. The remaining steps were the same as in Example 1, and lutein-zein nanoparticles ZLut-TZ-3 encapsulated by a metallophenol network were obtained.
[0030] Comparative Example 1 To investigate the effects of different systems on the properties of nanoparticles, a free-Zein nanoparticle group was set as a control for subsequent research.
[0031] Preparation method of Free-Zein: Add 2.5 g of zein powder to 100 mL of ethanol aqueous solution (volume concentration of 75%) to a final concentration of 2.5% (w / v), and stir magnetically until a stable protein dispersion is formed; slowly inject 1 mL of the dispersion into 10 mL of deionized water using a syringe, and hydrate for 120 min; after sufficient hydration, remove the ethanol from the system by rotary evaporation to obtain a pure zein nanoparticle dispersion, and then freeze-dry at -80℃ to obtain free zein nanoparticles.
[0032] Comparative Example 2 To investigate the effects of different systems on the performance of nanoparticles, a free-Lut nanoparticle group was set up as a control for subsequent research.
[0033] Free-Lut preparation method: 5.42 mg of lutein powder was dissolved in 100 mL of 75% (v / v) ethanol aqueous solution to obtain lutein dispersion, and then freeze-dried at -80℃ to obtain free lutein nanoparticles.
[0034] Comparative Example 3 To investigate the effects of different systems on the performance of nanoparticles, the unencapsulated lutein nanoparticle group (Zein-TZ) was set as a control for subsequent research.
[0035] Zein-TZ preparation method: First, a zein nanoparticle dispersion (without lutein) was prepared according to the method of the Free-Zein group. The dispersion was then taken and an equal volume of a 1% (w / v) tannic acid aqueous solution (the mass ratio of zein to tannic acid was 10:1) was added. Then, an equal volume of twice the concentration of ZnCl2 solution was added. Through blending and self-assembly, a Zein-TZ nanoparticle dispersion was formed. This was then freeze-dried at -80℃ to obtain lutein-free nanoparticles.
[0036] Comparative Example 4 To investigate the effects of different systems on the performance of nanoparticles, the lutein-zein nanoparticle group (ZLut-C) was set as a control for subsequent research.
[0037] ZLut-C Preparation Method: First, 2.5 g of zein powder was added to 100 mL of ethanol-water solution (75% v / v) to a final concentration of 2.5% (w / v), and magnetically stirred to form a stable protein dispersion. Lutein powder was added at a zein:lutein mass ratio of 45:1 under light-protected conditions, and the mixture was magnetically stirred overnight. Next, 1 mL of the above dispersion was slowly injected into 10 mL of deionized water using a syringe, and hydration was carried out for 120 min. After complete hydration, the ethanol in the system was removed by rotary evaporation to obtain a ZLut-C nanoparticle dispersion, which was then freeze-dried at -80℃ to obtain lutein-zein nanoparticles.
[0038] 2. Analysis of the formation of lutein-zein nanoparticles This invention determines the formation of nanoparticles by measuring the particle size, dispersion, and microstructure of lutein-zein nanoparticles, and evaluates the stability of the nanodispersion system by measuring the zeta potential; it evaluates the carrying capacity and economic efficiency of the nanosystem for loading lutein by measuring the encapsulation rate and loading capacity of lutein; and it confirms that the metallophenol network is wrapped on the surface of the nanoparticles by observing the surface distribution of Zn elements through scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS).
[0039] (1) Particle size and ζ-potential The particle size, zeta potential, and dispersion (PDI) of the ZLut-TZ-1, ZLut-TZ-2, and ZLut-TZ-3 nanoparticles prepared in Examples 1-3 were determined using a nanolaser particle size analyzer. All measurements were performed at 25°C, and the average of three measurements was taken. The ZLut-C nanoparticles prepared in Comparative Example 4 were used as a control for comparison.
[0040] like Figure 2 As shown in Figure A, compared with the control group ZLut-C nanoparticles (111.95 nm), the average particle size of nanoparticles ZLut-TZ-1 (100.3 nm) and ZLut-TZ-2 (100.17 nm) was slightly reduced. This is because the low-concentration metallophenol network is only a discontinuous thin layer, and its effect on the expansion or contraction of the particle core is limited by physical adsorption rather than chemical bonding of zein. The metallophenol network preferentially fills the concave areas on the particle surface, thus slightly reducing the apparent particle size. At the same time, PDI and particle size show the same trend. This is because the difference in interfacial tension between the metallophenol network and the particles leads to micro-phase separation, forming local high-energy regions, promoting the directional alignment of nanoparticles, and making the system more homogeneous. However, the average particle size and PDI of nanoparticle ZLut-TZ-3 increased significantly. This is because the metallophenol concentration is too high, forming a multilayer network on the protein surface. The electrostatic repulsion between nanoparticles is weakened, the steric hindrance is insufficient, and slight protein aggregation occurs, resulting in poor system stability and hindering the delivery of lutein. An increase in the absolute value of the ζ-potential indicates enhanced electrostatic repulsion between particles, thereby improving the stability of the system. In this invention, the pH of all nanoparticles was maintained between 4.0 and 5.0. This is because, under weakly acidic conditions of pH 4.0-5.0, hydrophobic interactions provide the driving force for particle assembly, while reduced electrostatic repulsion prevents excessive particle aggregation, thus enabling zein to form a stable nanoparticle structure.
[0041] Figure 2All nanoparticles in group B are positively charged. The control group, ZLut-C nanoparticles, has a potential of +14.97 mV. This is because the isoelectric point of zein is approximately 6.0-6.5, and the protein surface carries a positive charge when the solution pH is below the isoelectric point. Compared to ZLut-C nanoparticles, the absolute values of the ζ-potentials of ZLut-TZ nanoparticles are significantly increased, with ZLut-TZ-1 having the highest absolute value of +27.167 mV. This indicates that the metallophenol network encapsulating the zein surface helps improve the stability of the system. Compared to ZLut-TZ-1, the absolute values of the potentials of ZLut-TZ-2 (+23.367 mV) and ZLut-TZ-3 (+14.967 mV) gradually decrease. This is because when the metallophenol concentration exceeds a certain critical value, the hydrophobic interactions between zein molecules increase, leading to particle aggregation, a decrease in effective specific surface area, and a reduction in the exposed proportion of surface charged groups. Simultaneously, free ions (such as Na+) in the system... + H + The concentration of ζ-potential increases with the total amount of solute, which weakens the electric double layer thickness through the charge shielding effect, resulting in a decrease in the ζ-potential value.
[0042] (2) Encapsulation rate and loading capacity of lutein The ZLut-TZ-1, ZLut-TZ-2, and ZLut-TZ-3 nanoparticle sample dispersions prepared in Examples 1-3 were centrifuged at 5199 × g for 15 min. The precipitate at the bottom of the centrifuge tube was dissolved in 75% (v / v) ethanol aqueous solution. The absorbance was measured at 445 nm using a UV-Vis spectrophotometer, and the absorbance was determined according to the lutein standard curve (c=134Abs-0.01; R). 2 =0.991) The content of free lutein was calculated, with ZLut-C nanoparticles prepared in Comparative Example 4 used as a control for comparison. The encapsulation efficiency (EE) and loading capacity (LC) of lutein were calculated according to Equations 1 and 2: (Equation 1) (Equation 2) Figure 3 The effects of different concentrations of metallophenol networks on the encapsulation efficiency and loading capacity of lutein were demonstrated. When the zein-to-lutein mass ratio was 45:1, ZLut-C nanoparticles exhibited a high encapsulation efficiency (EE exceeding 80%). The encapsulation efficiencies of lutein in ZLut-TZ-1 and ZLut-TZ-2 nanoparticles were 87.71% and 91.69%, respectively, significantly higher than the 85.6% encapsulation efficiency of the ZLut-C control group nanoparticles. p<0.05). This further demonstrates that the formation of metal-phenol networks at low concentrations can significantly increase the encapsulation of lutein, for the following reasons: (1) The metal-phenol network (MPN) is formed by the self-assembly of metal ions and polyphenols, and its porous structure provides a large specific surface area and loading space, which can reduce the physical leakage of lutein; (2) As a polyphenol, TA has strong antioxidant capacity, which delays the oxidation and degradation of lutein nano-dispersion in the air; (3) Zn 2+ It can quench free radicals, reduce the risk of lutein oxidation, and has a certain stabilizing effect. In addition, compared with ZLut-TZ-2, the encapsulation rate of ZLut-TZ-3 dropped rapidly to 81.68%, which is due to the increased concentration of metallophenols, reduced carrier stability, and unfavorable delivery and encapsulation of lutein.
[0043] Furthermore, load capacity primarily focuses on the economic efficiency and practicality of the carrier. Meanwhile... Figure 3 The addition of metal-polyphenols resulted in a slight decrease in the system's loading capacity. This may be due to the increased amount of carrier material and the fact that the metallophenol network stabilizes the particles through electrostatic self-assembly, resulting in a less tight material bond. Considering the particle size, potential, encapsulation, and loading capacity of the nanoparticles, ZLut-TZ-1 and ZLut-TZ-2 are more stable and have a more homogeneous system compared to ZLut-TZ-3. Therefore, ZLut-TZ-1 and ZLut-TZ-2 were chosen for further morphological and functional characterization.
[0044] (3) Observation of the microstructure of nanoparticles The surface morphology of the nanoparticles was observed using field emission scanning electron microscopy. The lyophilized powders of ZLut-TZ-1, ZLut-TZ-2, and ZLut-TZ-3 nanoparticles prepared in Examples 1-3 were directly coated onto conductive adhesive and sputtered with gold. The morphology and structure of the nanoparticles were then observed using field emission scanning electron microscopy. Furthermore, the state of Zn, C, N, and O elements on the nanoparticle surface was observed using thermal field emission scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) to observe the formation of the metallophenol network on the nanoparticle surface. The Free-Zein nanoparticles prepared in Comparative Example 1 and the ZLut-C nanoparticles prepared in Comparative Example 4 were used as controls for comparison.
[0045] The microstructure of nanoparticles was observed using transmission electron microscopy (TEM). The sample preparation steps were as follows: the sample dispersion was dropped onto a copper grid, allowed to air dry overnight, and then the morphology and structure of the nanoparticles were observed under a transmission electron microscope. Figure 4As shown in Figure A, observations using a 500 nm scale cold field scanning electron microscope (SEM) revealed that Free-Zein, ZLut-C, ZLut-TZ-1, and ZLut-TZ-2 all exhibited uniform spherical shapes, confirming the formation of spherical nanoparticles. Among them, ZLut-C showed a small number of amorphous aggregates, while ZLut-TZ-1 and ZLut-TZ-2 displayed a tightly connected network structure. Compared to ZLut-C, ZLut-TZ nanoparticles were smaller, denser, and more uniformly distributed, consistent with the particle size results. This is because the formation of the metallophenol network not only helps stabilize individual protein particles, but the hydrogen bonds and intermolecular forces between Zein-TA also enhance the tight connections between multiple protein nanoparticles. SEM-EDS scanning of the surface of ZLut-TZ-1 nanoparticles revealed that Zn, O, and N were uniformly dispersed on the nanoparticle surface, indicating that the metallophenol network successfully coated the surface to form a rigid network. Figure 4 B). Figure 4 C is a TEM image at a scale of 500 nm, where the black circles represent nanoparticles. Among them, the ZLut-C nanoparticles have the largest particle size and are the most sparse. With the increase of metallophenol concentration, the particle size of ZLut-TZ-1 and ZLut-TZ-2 nanoparticles decreases and their density increases, which is consistent with the SEM image results.
[0046] 3. Structural analysis of lutein-zein nanoparticles (1) Fluorescence spectrum The intrinsic fluorescence of lutein-zein nanoparticles was measured at room temperature using a fluorescence spectrophotometer. Additionally, Free-Lut prepared in Comparative Example 2 was used as a control group, and the fluorescence spectra of Free-Zein and ZLut-TZ (i.e., ZLut-TZ-1 prepared in Example 1) were measured simultaneously to determine the fluorescence spectra among different nanoparticle groups. The excitation wavelength was set to 280 nm, the emission wavelength range was 290-450 nm, and the slit width was 5 mm. The average of three runs was taken for each emission spectrum.
[0047] Zeaxylose molecules contain high levels of aromatic amino acid residues such as tryptophan and tyrosine, and changes in the microenvironment of these residues significantly affect fluorescence properties. Since changes in the concentration of metallophenols do not alter the interaction types between the components of the nanoparticles, this invention selects ZLut-TZ-1 as a representative sample. Figure 5 (Represented as ZLut-TZ in Chinese), fluorescence properties were observed, and component interactions were analyzed. It was found that zein in ethanol-water exhibited a fluorescence emission peak at approximately 360 nm in the absence of added lutein. Fluorescence spectroscopy results ( Figure 5The results showed that the addition of a metallophenol network and the embedding of lutein gradually reduced the fluorescence emission intensity at 360 nm, while no blue shift or red shift was observed. This indicates that both lutein and metallophenol interact with the amino acid residues in zein, resulting in cross-linking. Furthermore, the fluorescence quenching effect of ZLut-TZ nanoparticles was stronger than that of Zein-TZ nanoparticles, suggesting that lutein and the metallophenol network synergistically interact with tyrosine residues in zein. These results indicate that lutein binds to zein through hydrophobic interactions or covalent bonds, altering the protein's secondary structure, and can synergistically lead to fluorescence quenching with the metallophenol network.
[0048] (2) Fourier transform infrared spectrum The interactions between the components in the nanoparticles were investigated using Fourier transform infrared spectroscopy (FTIR). Pure potassium bromide (KBr) powder was used as the measurement background. 1.0 mg of lyophilized sample powder was mixed with 100 mg of KBr powder, ground, and compressed into tablets. Measurements were taken at 4000–400 cm⁻¹. -1 Within the wavenumber range of 4 cm -1 Spectral data is collected at a high resolution.
[0049] The interactions between the components of the nanoparticles were further analyzed using FTIR spectroscopy. The FTIR spectra of Free-Lut, Free-Zein, and Zein-TZ, ZLut-C, and ZLut-TZ composite nanoparticles are shown below. Figure 6 As shown (ZLut-TZ-1 is also used as the representative sample here), Figure 6 (Represented as ZLut-TZ in Chinese). The Free-Zein group is located at 3307.91, 2960.72, 1658.77, 1537.26, and 1240.22 cm⁻¹. -1 Characteristic absorption peaks are observed at [values missing], corresponding to hydroxyl stretching vibration (OH), methylene symmetric stretching vibration (CH), ester group characteristic absorption (CO), and coupled vibrational modes of amide I bond (C=O) and amide II bond (NH / CN). The characteristic peaks of the ZLut-C group shift to 3311.76, 2960.72, 1654.92, 1537.26, and 1240.22 cm⁻¹, respectively. -1Furthermore, it was found that some characteristic absorption peaks of lutein in ZLut-C nanoparticles did not show obvious signals. This indicates that lutein molecules are embedded in the tertiary structure cavity of the protein matrix through hydrophobic interactions, rather than simply adsorbed on the particle surface. This proves the effective encapsulation of lutein by the corn protein carrier. Comparing the changes in the spectral absorption peaks of ZLut-C and Free-Zein, it was found that the characteristic peak related to hydroxyl groups shifted significantly, while other peaks did not change significantly. This indicates that lutein and zein are mainly linked through hydrogen bonds, leading to changes in protein conformation. Compared with Free-Zein, Zein-TZ nanoparticles showed significant changes at 3311.76, 2960.72, 1658.77, 1535.33, and 1201.65 cm⁻¹. -1 The presence of characteristic peaks indicates that the metallophenol network modifies and links zein via hydrogen bonding and electrostatic interactions. Furthermore, for ZLut-TZ nanoparticles, FTIR spectra show peaks at 3311.76, 2960.72, 1658.77, 1535.33, and 1203.58 cm⁻¹. -1 The presence of a characteristic absorption peak indicates that the metallophenols do not form new covalent bonds with the lutein molecules, but rather form coordination bonds or hydrogen bonds with polar groups such as hydroxyl and ketone groups, thereby enhancing the anchoring effect of lutein in the encapsulation process.
[0050] 4. Stability analysis of lutein-zein nanoparticles (1) Thermal stability Take 10 mL of the nanoparticle dispersion and place it in a 25 mL transparent bottle. Heat the bottle in a water bath at 80℃ and 37℃ for 2 h, cool it to room temperature, and then determine the retention of lutein. Figure 7 The results showed that lutein retained well after heat treatment at 37℃ for 120 min (retention rate ≥70%), but significant degradation occurred after treatment at 80℃ for 120 min. After treatment at 37℃ for 120 min, the retention rates of lutein in ZLut-C, ZLut-TZ-1, and ZLut-TZ-2 were 72.68±0.34%, 79.56±0.36%, and 79.25±0.56%, respectively. These results confirm that lutein can maintain a relatively stable content at 37℃, and the presence of the metallophenol network helps improve the thermal stability of lutein. Meanwhile, 80℃ was used to simulate the temperature of food heat processing. After treatment at 80℃ for 120 min, the retention rates of lutein in ZLut-C, ZLut-TZ-1, and ZLut-TZ-2 were 33.25±0.49%, 61.01±0.10%, and 61.91±0.65%, respectively. The results showed that zein, as a carrier, can protect lutein from thermal degradation, but the heat resistance of protein nanoparticles is still limited. In contrast, metallophenol network can significantly enhance the thermal stability of lutein nanoparticles when treated at higher temperatures.
[0051] (2) Storage stability To determine the chemical stability of lutein during storage, 10 mL of nanoparticle dispersion was placed in 25 mL transparent bottles and stored for 15 days under natural light at 25°C and in a refrigerator at 4°C. The retention rate of lutein was measured every 3 days. The retention rate of lutein in the nanoparticle samples was evaluated during the 15-day storage at 4°C and 25°C. Figure 8 A and Figure 8 (B) After 15 days of storage, the retention rates of lutein in ZLut-C, ZLut-TZ-1, and ZLut-TZ-2 were 71.15±1.67%, 80.56±1.30%, and 81.6±1.40% under storage conditions at 4℃, respectively; and 59.91±3.0%, 84.20±0.62%, and 82.13±1.40% under storage conditions at 25℃, respectively. These results indicate that the metallophenol network can significantly alleviate the degradation of lutein nanoparticles and improve storage stability. This is because the metallophenol coordination network has a uniform structure and small intermolecular gaps, reducing the penetration of external factors such as oxygen and moisture, delaying the oxidation and degradation of lutein, and preventing the aggregation and precipitation of protein nanoparticles. Furthermore, ZLut-TZ-2 showed high efficiency in encapsulating lutein in the early stage (0-6 days), while the low-concentration metallophenol-encapsulated nanoparticles ZLut-TZ-1 showed better storage performance in the later stages. This may be because although high-concentration metallophenol networks can improve the encapsulation rate, their wall structure is too rigid, making them prone to cracking during storage due to environmental changes (such as humidity and temperature), which accelerates lutein leakage. In contrast, low-concentration metallophenol networks maintain long-term stability through a flexible network.
[0052] (3) Salt ion stability Different concentrations of NaCl were added to the nanoparticle dispersion, with NaCl concentrations set at 0, 25, and 50 mmol / L, and the mixture was homogeneous. The salt stability of the nanoparticles was evaluated by particle size, zeta potential, and lutein retention rate. The results of thermal and storage stability showed that ZLut-TZ-1 exhibited strong resistance to external disturbances, and it was selected as a representative sample for further salt ion stability studies. Figure 9 (Represented as ZLut-TZ in Chinese). The particle size, zeta potential, and lutein retention rate of nanoparticles under different ionic strengths are shown in the figure. Figure 9 As shown, with increasing ionic strength, both the prepared nanoparticles ZLut-C and ZLut-TZ exhibit increased particle size and decreased absolute ζ-potential, leading to instability and turbidity in the system. This is attributed to the high concentration of salt ions (Na+). + Cl -Electrostatic shielding can weaken the electrostatic repulsion between molecules, thereby accelerating particle aggregation. Furthermore, compared to ZLut-C, ZLut-TZ exhibits superior stability across various ion concentration ranges. When the NaCl concentration is 50 mmol / L, the average particle size, zeta potential, and lutein retention rate of ZLut-C nanoparticles are 149.1 nm, +6.62 mV, and 77.33%, respectively, while those of the ZLut-TZ nanoparticle group are 144.6 nm, +14.4 mV, and 81.16%, respectively. This demonstrates that the nanoparticles encapsulated by the metallophenol network exhibit enhanced salt tolerance of lutein.
[0053] (4) pH regulation ability to release lutein The pH of the nanoparticle dispersion was adjusted to 3 and 7 using 1 M HCl or NaOH solution. The particle size, zeta potential, and lutein retention rate of different nanoparticles were determined using a nanolaser particle size analyzer. All measurements were performed at 25℃, and the results are the average of three measurements. ZLut-TZ-1 was used as a representative sample in the study. Figure 10 (Represented as ZLut-TZ in Chinese). The pH of ZLut-C and ZLut-TZ nanoparticle solutions is between 4 and 5. The solutions are adjusted to pH=3.0 and pH=7.0 using hydrochloric acid / NaOH solution to simulate the gastrointestinal environment. Figure 10 The average particle size, zeta potential, and lutein retention of ZLut-C and ZLut-TZ are shown under pH 3.0 and 7.0 conditions. Figure 10 A shows that the particle sizes of ZLut-C and ZLut-TZ at pH=3 were 127±2.45 nm and 121.03±3.75 nm, respectively, while at pH=7 they were 139±2.65 nm and 406.13±2.56 nm, respectively. This indicates that under acidic conditions, the nanoparticles are slightly smaller and more uniform, forming a tight and stable three-dimensional network structure, resulting in well-dispersed small particle aggregates. Conversely, under neutral or weakly alkaline conditions, the nanoparticle size increases, which is attributed to the weaker coordination of their metallophenol network and the looser structure. This structural change can drive the controlled and sustained release of lutein from the carrier. Figure 10 B shows that the absolute value of the ζ-potential of ZLut-TZ was higher than that of the control group ZLut-C at pH=3 and pH=7, indicating that the metallophenol network helps to improve the stability of nanoparticles under different pH conditions. Figure 10C indicates that both types of nanoparticles can maintain a high lutein retention rate in an acidic environment at pH=3, because zein, as a nanocarrier, has a certain resistance to acidic environments. Meanwhile, under neutral conditions at pH=7, the lutein retention rate of the ZLut-TZ group was also significantly higher than that of the ZLut-C group. This is because the tannins and zinc ions in the metallophenol network have excellent free radical scavenging and antioxidant capabilities, which can provide in-situ protection for the lutein slowly released from the carrier, preventing its oxidative degradation in the intestinal digestive environment. This significantly increases the total amount of effective lutein that can be absorbed by the intestines, laying the foundation for improved bioavailability.
[0054] 5. Analysis of the digestibility characteristics of lutein-zein nanoparticles The bioavailability of lutein was determined through in vitro simulated gastrointestinal experiments. Considering the short oral digestion time and low protease content in saliva, this invention did not simulate oral digestion, but primarily simulated gastric and intestinal digestion. First, the pH of 10 mL of lutein nanoparticle sample dispersion was adjusted to 3 with 1M HCl solution. Then, 10 mL of simulated gastric digestion solution (pepsin activity 2000 U / mL, calcium chloride 15 mM) was added and incubated at 37°C and 100 rpm for 60 min to simulate gastric digestion. After 60 min of incubation, the pH of the mixture was adjusted to 7 with 1M NaOH solution, and then 20 mL of simulated intestinal digestion solution (calcium chloride 0.6 mM, trypsin activity 100 U / mL) was added. The mixture was then incubated at 37°C and 100 rpm for 60 min to simulate small intestinal digestion. After digestion, 2 mL of the digestion solution was collected and centrifuged at 5199 ×g for 15 min. The supernatant was the micelle phase, and the uncentrifuged digestion solution was named the total digestion solution. The absorbance at 445 nm was measured to determine the lutein content in the sample. The bioavailability of lutein in different nanoparticles was calculated using Equation 3. Bioaccessibility ): (Equation 3) Among them, C Micelle and C Initial The values represent the lutein concentrations (mg / mL) in the micelle phase and the original digestion solution, respectively.
[0055] Figure 11The results showed that the bioavailability of lutein in different nanoparticles was ZLut-TZ (88.0±2.5%) > ZLut-C (77.5±1.2%) > Free-Lut (33.9±2.1%). This indicates that free lutein itself has extremely low bioavailability and is easily degraded by bile salts and digestive enzymes during gastrointestinal digestion. However, lutein nanoparticles constructed using zein as a carrier significantly improved the bioavailability of lutein. p <0.05), with the ZLut-TZ group showing the most significant improvement. Its core mechanism of action is as follows: In the acidic digestive environment of the stomach, the encapsulation of the metallophenol network plays a protective role. This network has a dense three-dimensional mesh structure, stable chemical properties, and good spatial barrier effect, which can mask the binding sites between pepsin and zein, inhibiting the hydrolysis of carrier proteins by pepsin, thereby delaying the premature release and degradation of lutein in the stomach. Simultaneously, the metallophenol network itself has a certain pH regulation ability, which can also improve the encapsulation rate and stability of lutein, further promoting the dissolution of lutein in digestive fluid nanomicelles. In a simulated intestinal digestive environment, the weakly alkaline environment weakens the effect of the metallophenol network, accelerating the release and absorption of lutein in the intestine. This selective release behavior of lutein enhances its bioavailability after gastrointestinal digestion, thereby improving the stability and bioactivity of lutein.
[0056] In summary, this invention provides a method for preparing lutein-zein nanoparticles encapsulated by a metallophenol network. The method includes obtaining a lutein-zein nanodispersion using an antisolvent method and rotary evaporation, then preparing ZLut-TZ nanodispersions of different concentrations by simultaneously adding ZnCl2 and TA solutions and utilizing a molecular self-assembly method. Finally, the nanoparticles (ZLut-TZ) are obtained by freeze-drying at -80°C. The low concentration of the metallophenol network helps enhance the thermal stability, storage stability, and salt ion stability of the nanoparticles. Specifically, ZLut-TZ-1 exhibits strong resistance to environmental disturbances, while ZLut-TZ-2 demonstrates high lutein loading efficiency. Furthermore, the metallophenol network endows the nanoparticles with a certain pH regulation capability. Under acidic conditions, the nanoparticles are smaller and more compact, providing efficient protection for the encapsulated lutein and preventing premature leakage and degradation in the stomach. Under neutral (or weakly alkaline) conditions, the nanoparticle size increases, and the metallophenol network structure becomes more loose, thus achieving controlled and sustained release of lutein into the intestine. Simultaneously, the tannins and zinc ions in the metallophenol network protect the released lutein from oxidative degradation, greatly improving the intestinal bioavailability of lutein. This invention has a simple preparation process, is easy to industrialize, and has broad application prospects in the protection and delivery of carotenoids and the development of related functional foods.
[0057] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for the preparation of metallophenol network encapsulated lutein-zein nanoparticles, characterized in that, The method comprises the following steps: (1) using anti-solvent method, corn protein powder is dissolved in solvent to prepare a solution, stirring uniformly, adding lutein, stirring to obtain a dispersion; taking the dispersion, adding water, hydrating for 100-140 min, rotary evaporation to obtain lutein-corn protein nanoparticle dispersion; (2) taking the dispersion obtained in step (1), adding tannic acid solution, then adding ZnCl2 solution, mixing to obtain sample dispersion, freeze-drying to obtain metal phenol network wrapped lutein-corn protein nanoparticle ZLut-TZ.
2. The production method according to claim 1, characterized by, The solvent in step (1) is 65-85% ethanol solution.
3. The production method according to claim 2, characterized by, In step (1), corn protein powder is dissolved in ethanol solution to a final concentration of 1.5-3.5%.
4. The production method according to claim 1, characterized by, In step (1), lutein is added in a mass ratio of (25-65):(0.5-1.5) to lutein.
5. The preparation method according to claim 1, characterized in that, The hydration reaction time in step (1) is 120 min.
6. The method of claim 1, wherein, In step (2), the dispersion is added to an equal volume of tannic acid solution with different concentrations; the concentration of the tannic acid solution is set in a mass ratio of (5-15):(0.5-2.5) to corn protein:tannic acid.
7. The preparation method according to claim 1, characterized in that, In step (2), ZnCl2 solution is added in an equal volume and twice the concentration of tannic acid.
8. A metal phenol network wrapped lutein-corn protein nanoparticle obtained by the preparation method of any one of claims 1-7.
9. The use of the metal phenol network wrapped lutein-corn protein nanoparticle of claim 8 in the food field.